Shamans of Scientism: Conjuring Certainty Where There Is None - Bauer, Henry (Journal of Scientific Exploration, 2014)
<span style="font-size: 11.0pt; mso-bidi-font-size: 10.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Some vociferous proponents of established science assert that it should always be believed when there are controversies over issues of public importance. That assertion rests on three assumptions, none of which are usually made explicit: 1) that only science is capable of arriving at truths about the natural world and that it actually does so; 2) that “science” is identical to the views propounded by the contemporary prevailing establishment of science, its mainstream institutions; and 3) that science can be distinguished unequivocally, with certainty, from everything else. None of those presumptions has been demonstrated to be correct, and indeed there are excellent historical and logical reasons to regard all of them as wrong. Since these underlying assumptions cannot be proven, self-styled “skeptics” and other activists who seek hegemony for contemporaneous scientific consensuses engage in intellectual and rhetorical misdirection to give actual uncertainty the appearance of “practical” certainty. In doing so, activists fail to acknowledge the crucial distinction between a point of view that appropriately guides scholarly discourse or scientific research and views (expert opinions or assertions or conclusions) that “everyone” should accept and that offer appropriate guidance to public policies and actions.